2010
DOI: 10.3109/14767058.2010.482602
|View full text |Cite
|
Sign up to set email alerts
|

Renal glomerular and tubular function in neonates with perinatal problems

Abstract: In neonates, renal impairment, being multifactorial in origin, may be caused by the additive effect of different perinatal factors. The strong negative relationship observed between jaundice and K excretion merits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…8,14 In this study, apart from birth weight, all the significant laboratory findings were found within the second week of life, and these significant differences in the two groups were seen mainly in the electrolyte data reflecting the developing renal function in VLBW infants. In the nephrocalcinosis group, serum creatinine reflecting the renal glomerular function 16,17 significantly increased during weeks 1 and 2 of life compared with the control group. These results suggest that the nephrocalcinosis group had a greater decrease in glomerular function during the period compared with the control group.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…8,14 In this study, apart from birth weight, all the significant laboratory findings were found within the second week of life, and these significant differences in the two groups were seen mainly in the electrolyte data reflecting the developing renal function in VLBW infants. In the nephrocalcinosis group, serum creatinine reflecting the renal glomerular function 16,17 significantly increased during weeks 1 and 2 of life compared with the control group. These results suggest that the nephrocalcinosis group had a greater decrease in glomerular function during the period compared with the control group.…”
Section: Discussionmentioning
confidence: 83%
“…Increased serum calcium at 2 weeks of life in the nephrocalcinosis group is likely related to a more concentrated intravascular blood volume or dehydration as during the period there was a trend for increasing serum Na, though not reaching statistical significance; however, serum and urinary calcium have also been reported to be influenced mainly by nutrition status and postnatal age. 19 From these results the VLBW infants with nephrocalcinosis may have a greater decrease in renal tubular function due to the renal handling of electrolytes including calcium and sodium 16,17 compared with the VLBW infants without nephrocalcinosis within the first 2 weeks of life. Similar results were associated with impaired renal function within the first 2 weeks in VLBW infants with nephrocalcinosis supplemented with a fortifier and vitamin D, who showed metabolic acidosis within the first week of life and high renal calcium and phosphate excretion within the first 2 weeks, as reported by Hein et al 8 Because our subjects were not supplemented with a fortifier and vitamin D, the our results can be regarded as more accurate in reflecting the calcium metabolism.…”
Section: Discussionmentioning
confidence: 91%
“…Damaged tubular cells will produce and secrete biological substances that related to innate immune response and inflammation process including protein [7]- [9]. Neutrophil gelatinase-associated lipocalin (NGAL) is a protein that is secreted by immune cells, hepatocytes, and renal tubular cells.…”
Section: Introductionmentioning
confidence: 99%